Diagnostic challenges of FNA cytology of SETTLE: a case report and review of the literature - Evelyn O. Ilori; Hanan Hamdan; Venetia Sarode; Iram Hussain; Ana Islam; Justin A. Bishop (Diagnostic Pathology)
Abstract Background Spindle epithelial tumor with thymus-like differentiation or elements (SETTLE) is a rare and malignant biphasic tumor of the thyroid that has proven challenging to diagnose by cytology. Case presentation A 20-year-old-male presented with a large left neck nodule and neck tightness. Laboratory tests were normal. Computed Tomography (CT) of the neck revealed a thyroid mass involving the isthmus and entire left lobe. Ultrasound-guided fine needle aspiration of the mass demonstrated sheets and clusters of oval to spindle cells with associated fibrovascular cores. The cells had moderately pleomorphic nuclei with stippled chromatin, inconspicuous nucleoli, and minimal cytoplasm, and a diagnosis of medullary thyroid carcinoma was made. A total thyroidectomy and neck dissection was performed. Morphological and immunohistochemical evaluation of the specimen resulted in a diagnosis of SETTLE with angioinvasion and involved lymph nodes. Conclusion SETTLE has several mimics cytologically, such as medullary thyroid carcinoma, that makes accurate pre-operative diagnosis challenging. We present a review of cytology information from literature, highlighting features that differentiates SETTLE from its mimics.